Star Identification Methods, Techniques and Algorithms - Zhang, Guangjun (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book summarizes the research advances in star identification that the author's team has made over the past 10 years, systematically introducing the principles of star identification, general methods, key techniques and practicable algorithms. It also offers examples of hardware implementation and performance evaluation for the star identification algorithms. Star identification is the key step for celestial navigation and greatly improves the performance of star sensors, and as such the book include the fundamentals of star sensors and celestial navigation, the processing of the star catalog and star images, star identification using modified triangle algorithms, star identification using star patterns and using neural networks, rapid star tracking using star matching between adjacent frames, as well as implementation hardware and using performance tests for star identification. It is not only valuable as a reference book for star sensor designers and researchers working in pattern recognition and other related research fields, but also as teaching resource for senior postgraduate and graduate students majoring in information processing, computer science, artificial intelligence, aeronautics and astronautics, automation and instrumentation. Dr. Guangjun Zhang is a professor at the School of Instrumentation Science and Opto-electronics Engineering, Beihang University, China and also the Vice President of Beihang University, China.